Avatar, the last airbender : Azula in the spirit temple - Hicks, Faith Erin (Dark Horse Books, 2023)
"Azula continues her destabilizing campaign against the Fire Nation and her brother, Fire Lord Zuko. But after a failed attack on her latest target, Azula finds herself in a mysterious forest temple inhabited by a solitary monk...or is it something more mysterious? Azula must confront her past, and finally face her chance at redemption"--